ANALISIS UNSUR-UNSUR BAWAH SADAR NOVEL pABRIK BERDASARKAN TEORI SIKOANALISIS Analysis on the Subconscious Elements of Pabrik (Factory) Using Psychoanalytic Theory I - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT The study discusses the subconscious elements as embodied in Pabrik (fiction). It aims to reveal the id, ego, and superego as well as the meaning of subconsciousness. The result of the study shows that various types of id are found in the subconcious elements of the work. The id demanded fulfilments, but got stuck with the external factors, i.c., superego. While ego, could not afford to bridge the gap between the fulfilment of id and superego demands. In the subconscious elements of Pabrik, many animalistic disires are found in the characters so that they do many deviations, aspecially sexual and social deviation. Therefore, the description of community is full of madness. The sublime meaning of Pabrik is a criticsm againts the madness of community in the development under the guise of modernization and industrialization as a progress. However, it often leads to a catastrophe. Key words: community -- madness -- modernization